2021
DOI: 10.46328/ijemst.1827
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Predictors of Pre-Service Teachers’ Intention to Integrate Computer Games in Mathematics Education

Abstract: The purpose of this exploratory study was to examine whether specific attitudes and beliefs among pre-service teachers about the use of computer games in mathematics teaching and learning predict their intention to integrate computer games in future mathematics teaching. Data were collected via a questionnaire from 119 teacher education students in a mathematics methods class at a midwestern USA university. Findings indicate that previous experience of computer gaming, gamer identity, self-efficacy for compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Taheri et al (2021), in the study of the relationship between creativity and academic achievement, showed that there is a positive and significant relationship between the components of creativity and academic achievement. Liu et al (2022) examined the function of computer games in adolescent behavior, the results showed that there is no difference between the mental ability of students who use computer games compared to students who do not use it. Cheah et al (2022) examined the effect of computer games on the development and motivation of learning geography in primary school children and showed that computer games can be used as formal educational tools for this course in formal educational environments.…”
Section: Iranian Efl Computer Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taheri et al (2021), in the study of the relationship between creativity and academic achievement, showed that there is a positive and significant relationship between the components of creativity and academic achievement. Liu et al (2022) examined the function of computer games in adolescent behavior, the results showed that there is no difference between the mental ability of students who use computer games compared to students who do not use it. Cheah et al (2022) examined the effect of computer games on the development and motivation of learning geography in primary school children and showed that computer games can be used as formal educational tools for this course in formal educational environments.…”
Section: Iranian Efl Computer Gamesmentioning
confidence: 99%
“… Liu et al (2022) examined the function of computer games in adolescent behavior, the results showed that there is no difference between the mental ability of students who use computer games compared to students who do not use it.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…At the same time, teachers may view digital games as a distraction and not as advantageous for student practice as other tools, such as physical manipulatives. While some teachers believe that the games can be useful, they are not always viewed as the most beneficial tools of instruction and thus not always worth the time the games would take to incorporate into their teaching [30,31]. A fourth finding rests in the additional teaching load that including digital games brings for teachers, even amidst overall positive views of the use of digital games in the mathematics classroom more generally [29].…”
Section: Theoretical Framework: Teachers' Beliefs and Use Of Game-enh...mentioning
confidence: 99%
“…Even with positively held beliefs towards digital games, teachers occasionally hesitate to implement them in the classroom due to factors such as cost and an educational focus on increasing scores on standardized tests [33]. So, while beliefs held by the teacher about using digital games in math could indicate the likelihood of implementing them [32], it is not always the case [30,32].…”
Section: Theoretical Framework: Teachers' Beliefs and Use Of Game-enh...mentioning
confidence: 99%